Annular Hailey-Hailey disease - Ariane Fizazi; Olivier Dereure (Wiley, 2024)
Abstract Hailey-Hailey disease (HHD) is a genodermatosis that typically presents with crusted erosions located in skin folds and the perineum. We report two cases of a highly atypical form of HHD, characterised by inflammatory annular skin lesions on the trunk, isolated and sparing the folds in one patient. Diagnosis was confirmed by histology or genetic analysis. Clinicians should consider this exceptional subset of HHD when encountering annular lesions resistant to antifungals even when a relevant familial background is lacking.